História, literatura e cidade em Os condenados: a trilogia do exílio, de Oswald de Andrade – e outros fragmentos urbanos - Claudiano, Leonardo da Silva (2024)
This thesis aims to capture the São Paulo that Oswald de Andrade felt and preserved in his novel, Os condenados: a trilogia do exílio. By São Paulo, I do understand, in addition to the physical space, the sociability that develops in the urban scenario, as well as the changes in the subjective map of its inhabitants, in the face of the countless changes that collide. Faced with an irreversible and irresistible technological landscape, I am interested, in Oswald's writing, in the dialectical relationship with the city that seduces and threatens. I also remember that Os condenados was part of the Semana de Arte Moderna – that is, it is located in an instant of transition, between a time that dies and survives transmuted, and a time that emerges to constantly undo and remake itself, always charged of elements that preceded it. The fragmented form of the work aims to break with continuity; I intend to walk with bumps, the recurring shocks of the crowds. It seeks to be a city and represent the experience of modernity – understood as the conflicting fusion between modernization and modernism. Furthermore: when referring to modernity, I do so in its plural. In Os condenados, the encounter places these different times in negotiation, denial and imposition. In my research text, I also seek dialogue with memoirists and other writers, in the desire to collect urban perceptions and, with them, build the city through which Oswald de Andrade and his characters will walk, in agreements or dissonances. Finally, these lines were configured as a written exercise that operates on the widespread boundaries between History and Literature. There is subjectivity, approximation and a historian-utterer who is an active voice